Análisis de la oferta académica de las instituciones de educación superior de Cotopaxi y necesidades de estudios de posgrado de los docentes de bachillerato del cantón Latacunga. Diseño de un programa de posgrado en Ciencias de la Educación, para la Universidad Técnica de Cotopaxi. - Changotásig Masapanta, Luis Willian (2015)
The need of highly qualified teachers with fourth level is an undeniable fact face the development challenges of a globalized and highly competitive. The offer of an academic quality product is looking for new alternatives and strategies, techniques, methods and models date teaching learning. One of the many causes of professional frustration is the reduced supply of graduate programs in our province. The flexibility of the academic offer is a quality that is expressed in the way we operate the curriculum according to the needs and aspirations of professionals with tertiary qualifications in this way they will be able to work with the largest possible number of people. Graduate courses aim to expand and develop the knowledge to solve disciplinary, interdisciplinary or professional problems and give people the basic tools that enable a researcher in a specific area of science or technology that to deepen theoretical and conceptually in a field of philosophy, humanities and arts. The implementation of programs of Graduate Education in Ecuador is one of the most pressing for the harmonious development of the education system needs, since it is in the fourth level or postgraduate specialists from different areas are formed that a country needs. The lack of specialized programs in different educational areas has led to opt for postgraduate teachers in general educational areas. In surveys of high school teachers say it is necessary to offer graduate programs in specific areas of knowledge. For this reason a graduate program in Education Sciences with a major in Geography is designed.